2018
DOI: 10.3390/nu10101522
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a Short Diet Questionnaire to Estimate Dietary Intake in Older Adults in a Subsample of the Canadian Longitudinal Study on Aging

Abstract: This study assessed test-retest reliability and relative validity of the Short Diet Questionnaire (SDQ) and usability of an online 24 h recall among 232 participants (62 years ± 9.1; 49.6% female) from the Canadian Longitudinal Study on Aging (CLSA). Participants were asked to complete four 24 h dietary recalls (24HRs) using the Automated Self-Administered 24-h Dietary Assessment Tool (ASA24-Canada-2014), two SDQ administrations (prior to recalls one and four), and the System Usability Scale (SUS) for ASA24. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
5
19
0
Order By: Relevance
“…The observed Pearson's correlation coefficients for nutrients are very similar to those of FFQ validation studies conducted in older adults that also used multiple 24-hour dietary recalls as the reference method [19,20]. For example, their coefficients for energy, protein, fat, calcium, and fiber, respectively, ranged from 0.22 to 0.39, 0.30 to 0.41, 0.25 to 0.58, 0.38 to 0.54, and 0.29 to 0.50.…”
Section: Discussionsupporting
confidence: 67%
“…The observed Pearson's correlation coefficients for nutrients are very similar to those of FFQ validation studies conducted in older adults that also used multiple 24-hour dietary recalls as the reference method [19,20]. For example, their coefficients for energy, protein, fat, calcium, and fiber, respectively, ranged from 0.22 to 0.39, 0.30 to 0.41, 0.25 to 0.58, 0.38 to 0.54, and 0.29 to 0.50.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, Carter et al observed a lower SUS score for myfood24-UK in older adults (median SUS score = 29, n = 4 ≥ 65 years old) compared to younger age groups [5]. Further, feasibility testing for ASA24 in two different samples of elderly individuals showed that participants mostly preferred the traditional telephone-administered 24HDR [29] and the SUS score of 57 (SD 12.4, ASA24-Canada-2014) indicated poor usability [30]. The authors presumed that low computer literacy and limited Internet access narrow the ability to conduct self-administered 24HDRs online in older adults [29][30][31].…”
Section: Discussionmentioning
confidence: 93%
“…Further, feasibility testing for ASA24 in two different samples of elderly individuals showed that participants mostly preferred the traditional telephone-administered 24HDR [29] and the SUS score of 57 (SD 12.4, ASA24-Canada-2014) indicated poor usability [30]. The authors presumed that low computer literacy and limited Internet access narrow the ability to conduct self-administered 24HDRs online in older adults [29][30][31]. Our contrasting findings might be explained by the fact that only participants with Internet access were included in the evaluation study, and that the majority of participants had experience in using computers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A feasibility study of the Automated Self-Administered 24-hour dietary recall (ASA-24) among US adults 56–80 years of age highlighted the challenge of access: 60% invited reported no access to Internet, and adults 72–80 years of age were less likely than younger adults to have access to Internet/computer [12]. The ASA-24 (Canadian version) was used in a validation study among older adult Canadians, but participation results were not presented separately for relatively older and younger adults (over/under 65 years of age) [13]. Otherwise, feasibility studies have predominantly focused on adults younger than 70 years of age [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%